2017
DOI: 10.1007/s12032-017-1017-z
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of concurrent chemoradiotherapy comparing carboplatin/paclitaxel versus platinum/5-FU regimen for locally advanced esophageal and esophagogastric junction cancers

Abstract: Platinum/5-fluorouracil (PF) is commonly used for chemoradiotherapy (CRT) for locally advanced esophageal and esophagogastric junction (EGJ) cancers. Weekly carboplatin and paclitaxel (CP) regimen for preoperative CRT has increased in popularity due to its potentially less toxicity. We retrospectively compared the tolerability and efficacy of these regimens. Patients with esophageal and EGJ squamous cell carcinoma (SCC) or adenocarcinoma who received CRT with curative intent were included. Safety and tolerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria. Finally, a total of 31 articles involving 3432 participants were included [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The detailed retrieval process of this review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The relatively low toxicity profile of the CROSS regimen compared to PF while maintaining the same efficacy has made CROSS widely popular as nCRT in Western regions, mainly in response to esophageal adenocarcinoma [ 10 , 11 , 12 ]. While the subset of patients with ESCC in the CROSS trial showed promising findings (i.e., pathologically complete response [pCR] rate = 49%; median survival = 81.6 months), replication of these findings in Asia has not been successful [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The squamous cell carcinoma subtype accounts for approximately 90% of all esophageal cancers worldwide, and in Thailand. (Torre et al, 2015;Tamtai et al, 2017). The survival rates of most patients diagnosed with locally advanced disease range from 40% to 60% (Cheng et al, 2012;Di Fiore et al, 2006;Tamtai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(Torre et al, 2015;Tamtai et al, 2017). The survival rates of most patients diagnosed with locally advanced disease range from 40% to 60% (Cheng et al, 2012;Di Fiore et al, 2006;Tamtai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%